Les maisons gallo-romaines d'Ambrussum (Villetelle-Hérault) La fouille du secteur IV 1976-1980 - Fiches, Jean-luc (Documents d'archéologie française, 1986)
Relay-point on a roman road, the oppidum of Ambrussum is a major site concerning conditions and aspects of the romanisation in the region of Nîmes. Two houses with internal courtyards were already known and dated from the first century AD and form an insula of secteur I. Research conducted from 1976 to 1980 in secteur IV revealed a house of the same type with its dependancies. Following an analysis based on the conditions of implantation, occupation and abandonment, their architecture and distribution of the finds, these constructions appear to be an original expression of gallo-roman habitations. Situated in their local and regional contexts, they reflect the process of urbanisation and social differenciation, and of the village type exploitation existence.